Plant diversity and its conservation status in the Gunung Pujut Ancient Mosque Area, Lombok Island, Indonesia - Rahayu, Slamet Mardiyanto; Mappanganro, Nurlailah; Da Costa, Luis; Hakim, Luchman; Batoro, Jati; Sukenti, Kurniasih (Biogenesis: Jurnal Ilmiah Biologi, 2024)
Gunung Pujut Ancient Mosque is one of the cultural heritages in Lombok Island. This study aims to determine the diversity and conservation status of plants in the Gunung Pujut Ancient Mosque area. The research was conducted through direct observation, calculation of diversity index and dominance index, and tracing the conservation status of plant species. There are 29 families, 31 genera, and 34 plant species in the Gunung Pujut Ancient Mosque area. This is a stable ecosystem because it has a high diversity of plants. This shows that the cultural heritage area of the Gunung Pujut Ancient Mosque is a suitable habitat for the growth and development of various plant species and plays a role in supporting biodiversity conservation. There is no ecological pressure in this area because it has low plant dominance index.